Disparity Of Rokan Hilir District Court Decisions On Drug Crimes In 2024 - Anton Anton; Sriono Sriono; Nimrot Siahaan (CV. AFDIFAL MAJU BERKAH, 2025)
The method used in this article research is normative legal research, namely research on problems by looking at the sources of applicable regulations related to the title Disparity of Rokan Hilir District Court Decisions on Narcotics Crimes in 2024 The occurrence of disparities in sentencing basically starts from the sanctions contained in Law of the Republic of Indonesia No. 35 of 2009 concerning the Eradication of Narcotics Abuse, which opens up opportunities because there are minimum and maximum limits for sentencing, so that judges are free to move to get the punishment they think is appropriate. Application of criminal sanctions to perpetrators of actions. Drug Abuse based on several decisions in Indonesia is based on factors revealed in the trial, first the public prosecutor's indictment, second witness statements, third defendant's statement, fourth evidence and fifth based on articles in the legislation, Referring to the theory of justice, it can be said that the difference in imposing criminal sanctions on perpetrators of drug abuse has not touched the sense of justice either towards victims who feel disadvantaged, or towards the judge's verdict for perpetrators of drug abuse as stated in the opinion above. The difference in sentencing will have a negative impact on convicts who feel disadvantaged by the judge's decision if one convict compares him with another convict who is sentenced to a lighter sentence even though the crime committed is the same, the convict who is sentenced to a heavier sentence will become a victim of legal injustice so that the convict does not believe and does not respect the law;